Quantitative sources identification of gas emissions in mined-out area of coal seams in the Huanglong coalfield of the Ordos Basin, China - Bingyi Jia; Shugang Li; Haifei Lin; Dongdong Chen; Jingfei Zhang (Scientific Reports)
Abstract This study integrates different geochemical analyses (chemical compositions, carbon isotopes) and a physical mixing model to quantitatively identify gas sources and migration mechanisms in the Nanchuan No.2 coal mine. Results reveal distinct isotopic signatures: gases from mine-out area exhibit intermediate δC1 values (− 55.1‰ to − 49.6‰) between coal-seam methane (avg. δ13C1 = − 61.0‰) and Yanchang oil-type gas (avg. δ13C1 = − 49.7‰), indicating mixed origins. The mixing model quantifies oil-type gas contributions to goaf emissions as 74.3% (methane) and 75.5% (ethane), dominated by vertical migration from Triassic Yanchang Formation source rocks through mining-induced fractures. Low coal-seam gas content (avg. 0.97 m³/t) further supports external hydrocarbon influx. Structural heterogeneity in oil-type gas distribution correlates with spatial variations in contribution ratios (52.7–100%). Mining disturbances disrupt caprock integrity, creating pressure-relief pathways that drive gas migration via fracture networks. This work establishes a framework for optimizing gas control strategies in coal-oil-gas symbiotic systems, emphasizing the critical role of isotopic tracing in hazard mitigation.